Analisis Peran Perangkat Desa untuk Meningkatkan Akuntabilitas dalam Pengelolaan Dana Desa (Studi Kasus di Desa Sukarame Kec. Kualuh Hulu Kab. Labuhan Batu Utara) - Yuliana Yuliana; Tri Inda Fadhila Rahma; Nursantri Yanti (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
This study aims to find out how the role of village officials in Sukarame Village, Kualuh Hulu District, North Labuhanbatu Regency in the accountability of village fund management. The technique of collecting data is used by this panel of writers, namely by using interviews and documentation. The subjects of this research were cacahe ana 8 wong sing kalebu of Sukarame village officials, namely: Head of BPD, Village Head, Village Secretary, Village Treasurer, Head of Development, Head of Government, Head of General Affairs, and Head of Dusun. This Panliten uses a descriptive qualitative approach. The Panliten Sing was prosecuted, followed by the management of the Sukarame village apparatus, with full kanthi responsibilities for the 2020 period, this was proven by the involvement of the infographic board, which was installed to expect the village head's office. In addition to the village apparatus, they have carried out their respective responsibilities in each of their duties in terms of building facilities and infrastructure as evidenced by paving roads, constructing ditches.assistance for poor/achieving students, as well as transparency and openness of the village government as the manager of village funds to the community in the form of information on the use of funds. but because of the limited knowledge of the public who do not know anything about the infographic board in front of the village head's office and also indeed the implementation of the distribution of these funds is felt to be very slow, thus increasing the emergence of bad prejudice among the village community towards the village apparatus. This analysis is also supported by the fact that the education factor of the Sukarame village community is low and the ignorance of the village community. so overall the role of village officials is in accordance with the regulation of the minister of home affairs number 113 of 2014 which is managed in a transparent, accountable, participatory, orderly and budgetary discipline.